Analisis Pendapatan dan Kelayakan Pengembangan Usaha Tani Cap Tikus Kecamatan Motoling - Brigita Sengkey; Een N. Walewangko; Agnes L. Ch. P. Lapian (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the income and feasibility of rat stamp farming in Motoling District. Based on data obtained from 35 respondents, the average monthly revenue from the rat stamp business reached Rp.176,600,000, with an average total production cost of Rp.43,575,000. After calculating the cost of labor and raw materials, an average net income of Rp.2,755,000 per farmer per month was obtained. The business feasibility analysis using the R/C ratio method showed a value of 4.05, which indicates that every Rp.1 spent is able to generate revenue of Rp.4.05. With an R/C ratio of more than 1, rat cap farming in Motoling District is considered feasible and profitable to run. The results of this study recommend several development strategies, including increasing production efficiency, diversifying products, and strengthening marketing networks. In addition, it is recommended to establish a cooperative to support the collectivity of farmers in the purchase of raw materials and product marketing. Through the implementation of this strategy, it is hoped that the rat stamp farming business can improve the welfare of local farmers and have the potential for further development.